Antibacterial potency from the waste of durian rind (Durio zibethinus Murr.) against Propionibacterium acnes that causing acnes - Pratiwi, Made Mira; Kawuri, Retno; Ardhana, I Putu Gede (Jurnal Biologi Udayana, 2019)
One of the things that could cause pathogenesis of acne is the activity of normal flora bacteria on the skin, one of them is the bacteria Propionibacterium acnes . The use of extracts which is derived from severalparts of plant such as banana peel, mangosteen peel, dragon fruit peel, potato peel, crinum lily leaf, Marsh fleabane leaf, soursop leaf, soma leaf, green betle vine leaf, and cacao seed that are known to have antibacterial activity could help in acne healing attempt. This research was conducted at Microbiology Laboratory Faculty of Mathematics and Natural Sciences Udayana University from December 2017 until March 2018.The research was conducted with the intention toknow the appropriate solvent to obtain the compound type of durian rind extract dissolved with three types of solvent (methanol, ethanol, ethyl acetate), to look for the smallest resistor value (MIC) of the extract with a solvent that provides the best inhibitory power, and to know the compound type of the extract with a solvent that provides the best inhibitory power. The method is diffusion wells and phytochemical tests. The data that is obtained in the study were analysed by analysis of variance (ANOVA). In inhibition test against P. acnes , it is known that the durian rind ethyl acetate extract effectively showed the inhibitory effect on the bacteria growth, with MIC value of 1.1%. The compound that is contained in the durian rind ethyl acetate extract is terpenoid, steroid, flavonoid, phenolic, and tannin.